Realization of improved electrochemical performance for ZnCo2O4/C nanosheets through Ag coating. Issue 11 (1st June 2022) - Zhong, Linping; Luo, Yunan; Li, Ying; Yang, Yue; Wang, Xuejia; Zhou, Ting; Liu, Mengjiao; Zhao, Yan; Lai, Xin; Bi, Jian; Gao, Daojiang
Abstract: Regarded as a special transition metal oxide anode material, ZnCo2 O4 can offer a theoretical capacity of 975 mAh g −1, which is derived from the synergistic lithium storage of the conversion reaction and alloying process. Sadly, the large volume variation in repeated charge and discharge processes and poor intrinsic conductivity have obstructed its development and popularization. In this work, a series of Ag-coated ZnCo2 O4 /C nanosheet composites were synthesized via a facile thermal decomposition strategy. The XRD, SEM, EDS, and XPS results confirm that Ag has covered the surface of ZnCo2 O4 /C. The obtained Ag-coated ZnCo2 O4 /C nanosheet composites display better electrochemical performance than ZnCo2 O4 /C, and the coating amount of Ag plays an important role. When the coating amount of Ag is set as 0.05, it can reveal the best electrochemical performance among all the Ag-coated ZnCo2 O4 /C nanosheet composites and deliver a capacity of 679.8 mAh g −1 after 300 cycles. The enhancement of electrochemical performance should be attributed to the elevated conductivity caused by the Ag coating.